CRISPR interference of a clonally variant GC-rich noncoding RNA family leads to general repression of var genes in Plasmodium falciparum - Barcons-Simon, Anna; Cordon-Obras, Carlos; Guizetti, Julien; Bryant, Jessica M.; Scherf, Artur (mBio, 2020)
The human malaria parasite Plasmodium falciparum uses mutually exclusive expression of the PfEMP1-encoding var gene family to evade the host immune system. Despite progress in the molecular understanding of the default silencing mechanism, the activation mechanism of the uniquely expressed var member remains elusive. A GC-rich noncoding RNA (ncRNA) gene family has coevolved with Plasmodium species that express var genes. Here, we show that this ncRNA family is transcribed in a clonally variant manner, with predominant transcription of a single member occurring when the ncRNA is located adjacent to and upstream of an active var gene. We developed a specific CRISPR interference (CRISPRi) strategy that allowed for the transcriptional repression of all GC-rich members. A lack of GC-rich ncRNA transcription led to the downregulation of the entire var gene family in ring-stage parasites. Strikingly, in mature blood-stage parasites, the GC-rich ncRNA CRISPRi affected the transcription patterns of other clonally variant gene families, including the downregulation of all Pfmc-2TM members. We provide evidence for the key role of GC-rich ncRNA transcription in var gene activation and discovered a molecular link between the transcriptional control of various clonally variant multigene families involved in parasite virulence. This work opens new avenues for elucidating the molecular processes that control immune evasion and pathogenesis in P. falciparum. - IMPORTANCE Plasmodium falciparum is the deadliest malaria parasite species, accounting for the vast majority of disease cases and deaths. The virulence of this parasite is reliant upon the mutually exclusive expression of cytoadherence proteins encoded by the 60-member var gene family. Antigenic variation of this multigene family serves as an immune evasion mechanism, ultimately leading to chronic infection and pathogenesis. Understanding the regulation mechanism of antigenic variation is key to developing new therapeutic and control strategies. Our study uncovers a novel layer in the epigenetic regulation of transcription of this family of virulence genes by means of a multigene-targeting CRISPR interference approach.